A Computational Reverse Vaccinology Approach for the Design and Development of Multi-Epitopic Vaccine Against Avian Pathogen Mycoplasma gallisepticum - Mugunthan, Susithra Priyadarshni; Mani Chandra, Harish (Frontiers in Veterinary Science, 2021)
Avian mycoplasma is a bacterial disease causing chronic respiratory disease (CRD) in poultry industries with high economic losses. The eradication of this disease still remains as a challenge. A multi-epitope prophylactic vaccine aiming the antigenic proteins of Mycoplasma gallisepticum can be a capable candidate to eradicate this infection. The present study is focused to design a multi-epitope vaccine candidate consisting of cytotoxic- T-cell (CTL), helper- T-cell (HTL) and B- cell epitopes of antigenic proteins, using immunoinformatics strategies. The multi-epitopic vaccine was designed, its tertiary model was predcited, which was further refined and validated by computational tools. After initial validation, molecular docking was performed between multi-epitope vaccine construct and chicken TLR-2 and 5 receptors, which predicted effective binding. The results specify the structural stability, precise specificity and immunogenic response of the designed multi-epitope vaccine and it could be an appropriate vaccine candidate for the M. gallisepticum infection.